Buffalo’s Captured Imaginary: Atmosphere, Absurdity and the Depoliticized Imagination of the Rust Belt - Dincer, Evren M (SAGE Publications Inc, 2026)
Using Buffalo, New York, as a key case study, this article examines the cultural grammar through which the American Rust Belt is represented as a site of terminal decline and absurdity. Analyzing films, novels, and memoirs, it argues that a captured imaginary has taken hold, one that converts the systemic crises of deindustrialization into mood, tone, and atmosphere. Narratives of the region frequently deploy irony and absurdity as aesthetic strategies that depoliticize decline, stylizing it as an ambient condition rather than a structural problem to be contested. This representational pattern, often centered on white protagonists, displaces political critique and renders local agency incoherent. By framing these cities as uniquely dysfunctional and incapable of self-renewal, these cultural texts create the ideological conditions for external, technocratic intervention. The article concludes that this aestheticization of collapse is a political act that forecloses democratic possibility and captures the urban imaginary for outside management.
Keywords: Deindustrialization; Economic Development; Buffalo (New York); Aestheticization of Decline; Rust Belt; Captured Imaginary